PENGARUH BAP DAN NAA TERHADAP WAKTU PERTUMBUHAN TANAMAN KANTONG SEMAR (Nepenthes adrianii) SECARA IN-VITRO - Egi Nuryadin Nuryadin (Program Studi Pendidikan Biologi, FKIP Unpas, 2018)
Nepenthes adrianii (a carnivorous plant) is an endemic carnivorous plant of Mount Slamet, which is listed the convention on international trade of endangered species ( CITES). One potential posses Nepenthes adrianii the biological control of insects and plants medicine. The objectives of this study were to: 1) know concentration BAP and NAA optimal and know the time appear the emergence of shoots , roots and leaves. This research has been carried out experimentally. That stage of growth in bring up shoots, roots and leaves use a Completely Randomised Design on a two factors factorial pattern was used. The first factor was BAP concentrations with 4 levels 0 µM, 5 µM, 10 µM, and 15 µM. The second factor was NAA concentration with 4 levels 0 µM, 0,5 µM, 1 µM, and 1,5 µM. The research results showed germination of seeds in plants Nepenthes adrianii using media vacin and went (VW) with the addition of substance of a substance controller of growing BAP 4 mM produce quite a lot germination and treatment 10 mM BAP and 0,5 mM NAA is the fastest in time to occur , appear leaves and appear roots.